Tuberculosis and vitamin d [Tüberküloz ve D vitamini] - (:unkn) unknown (Marmara University, 2014)
Tuberculosis (TB) is still highly prevalent world-wide accounting for over one million deaths annually. Especially the multi drugresistant Mycobacterium tuberculosis necessitates the development of new agents to enhance the response to antimicrobial therapy for active TB. In the pre-antibiotic era, vitamin D was used to treat TB. However, after the development of antituberculosis agents, it lost its importance. Recently, its active metabolite, 1,25-dihydoxyvitamin D, was shown to enhance the immune response to mycobacteria. Vitamin D does not have a direct killing effect but 1,25-dihydoxyvitamin D, is a modulater of the immune system. The synthesis of 1,25-dihydroxyvitamin D promotes the production of endogen defensin and cathelicidin. These products have a direct lethal effect on bacteria and intracellular microorganisms like M.tuberculosis. In this review, the role of vitamin D in host resistance to M.tuberculosis infection and its effect for supplementation therapy is discussed. © 2014, Marmara University. All rights reserved.
Keywords: 1,25-dihydoxyvitamin D; Cathelicidin; Defensin; Immune response; Tuberculosis; Vitamin D